EFEKTIVITAS PENGGUNAAN APLIKASI TIK-TOK TERHADAP PERILAKU REMAJA DI PAGAR DEWA - Jemi Hastuti; Hafri Yuliani (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2022)
Social media is an internet-based communication media where users can continueto interact without any space and time limits that hinder human interaction. This researchis entitled “Effectiveness of the use of the Tik-Tok application on the Dewafence. Thepurpose of this study is to determine how the effectiveness of the use of the Tik-Tokapplication on the behavior of adolescents in the Dewa fence. This research method usesquanttitave methods. The toery used is the theory used is the theory of technologicaldetermination from McLuhan who assumes that every technologi created will createpatterns in humans, both communication pattrens and thinking behavior patterns, all ofthose patterns can be changed by the presence of new technology. Keywords: Application Tik-Tok, Social Imedia